Bias and variance of asymmetric double‐sided two‐way ranging. Issue 3 (13th August 2019) - Navrátil, Václav; Vejražka, František
Abstract: Asymmetric double‐sided two‐way ranging (ADS‐TWR) is a method of range estimation through precisely time‐stamped messages sent between two transceivers. In contrast to symmetric double‐sided two‐way ranging (SDS‐TWR), ADS‐TWR suppresses the errors induced by transceiver clock drifts even when the message reply delays are unequal. However, due to the nonlinearity of the ADS‐TWR estimator, its mean and variance cannot be evaluated in a straightforward or exact way. This article presents an analytical approach of evaluating an approximation of bias and variance of the range estimators and applies it on an exemplary set of parameters, typical for ultra‐wide band (UWB) localization systems. Moreover, the obtained results are verified by a Monte Carlo simulation. It will be proven that ADS‐TWR is safe to be used in most of the present applications, and its precision is rather similar to SDS‐TWR.